Compact, highly efficient ytterbium doped bismuthate glass waveguide laser - Mary, Rose; Beecher, Stephen; Thomson, Robert; Brown, Graeme; Jaque, Daniel; Ohara, Seiki; Kar, Ajoy (Optics Letters, 2012)
Laser slope efficiencies close to the quantum defect limit and in excess of 78% have been obtained from an ultrafast laser inscribed buried channel waveguide fabricated in a ytterbium-doped bismuthate glass. The simultaneous achievement of low propagation losses and preservation of the fluorescence properties of ytterbium ions is the basis of the outstanding laser performance.<br
Keywords: Ultrafast laser inscription; waveguide laser